Effects of comprehensive intervention on life quality among the elderly with Alzheimer Disease and their caregivers based on mixed models - Li Yang; Cheng Xuan; Caiyan Yu; Xiaoqing Jin; Pinpin Zheng; Jing Yan (Wiley, 2022)
Abstract Aims We conducted a multi‐sectoral comprehensive intervention for elderly Alzheimer Disease patients and their caregivers to improve their quality of life. Design Randomized controlled trial. Methods From June to June in 2019, 150 Alzheimer Disease patients were randomly selected from a nursing home in Zhejiang province of China, they were randomly divided into the intervention group and the control group. And they were given comprehensive and routine interventions respectively for six months. We used mixed models in our analyses to see how outcomes changed over time and how they were affected by the intervention, which could also solve the problems of missing values and data correlation. Results After six months, compared with the control group, the communication ability, housework handling ability, self‐care ability and life quality of the patients in the intervention group were improved, and the quality of life and caring ability of their caregivers were also significantly improved. Conclusion The multi‐sectoral collaborative care model proposed in this study integrated resources from several departments, effectively improved the quality of life of patients and their caregivers, and provided a way of care services for patients with Alzheimer Disease. Impact Multi‐sectoral comprehensive intervention would improve the life quality of elderly patients with Alzheimer Disease and their caregivers.